2009
DOI: 10.1007/s00436-009-1610-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant antigens in Naegleria fowleri excretory–secretory proteins were potential pathogenic factors

Abstract: Naegleria fowleri, a ubiquitous pathogenic freeliving amoeba, is the most virulent species and causes primary amoebic meningoencephalitis in laboratory animals and humans. The parasite secretes various inducing molecules as biological responses, which are thought to be involved in pathophysiological and immunological events during infection. To investigate what molecules of N. fowleri excretory-secretory proteins (ESPs) are related with amoebic pathogenicity, N. fowleri ESPs fractionated by two-dimensional ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
(25 reference statements)
1
23
0
1
Order By: Relevance
“…N. fowleri is a free-living amoeba that causes primary amoebic meningoencephalitis, a rare but acute and frequently fatal central nervous system disease. The genome has not yet been sequenced, but an 18-kDa Prx (matching a Prx1 from Aedes aegypti by its N-terminal sequence) was identified as an excretory-secretory pathogenic factor in N. fowleri infection (122). While it was not cloned and so may not be a Prx1, the sequenced genome of the nonpathogenic Naegleria gruberi (84) contains a Prx1 and a Prx5 (NCBI accession numbers XP_002678814 and XP_002680895, respectively).…”
Section: Prxs In Other Selected Protozoan Parasites Of Humansmentioning
confidence: 99%
“…N. fowleri is a free-living amoeba that causes primary amoebic meningoencephalitis, a rare but acute and frequently fatal central nervous system disease. The genome has not yet been sequenced, but an 18-kDa Prx (matching a Prx1 from Aedes aegypti by its N-terminal sequence) was identified as an excretory-secretory pathogenic factor in N. fowleri infection (122). While it was not cloned and so may not be a Prx1, the sequenced genome of the nonpathogenic Naegleria gruberi (84) contains a Prx1 and a Prx5 (NCBI accession numbers XP_002678814 and XP_002680895, respectively).…”
Section: Prxs In Other Selected Protozoan Parasites Of Humansmentioning
confidence: 99%
“…However, the precise mechanisms by which they exert their pathogenicity are unknown. Previous researches have suggested that infection may evoke both contact-dependent and contact-independent CNS pathology [7-11]. …”
mentioning
confidence: 99%
“…To elucidate the contact-independent mechanism for amebic pathogenicity, researchers have attempted to examine the cytopathic effects of incubating N. fowleri secreted proteins (excretory-secretory proteins; ESPs) or acanthamoebic lysate or their secreted proteins against a number of target cell types [9-11,14,15]. However, no studies have examined the specific effects of N. fowleri lysate on microglial cells in experimental models of PAM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the contact-dependent mechanisms, the Nfa1 protein and actin protein were characterized and identified in N. fowleri infections (11,30). In addition, excretory-secretory proteins (ESPs) released from N. fowleri have also been identified, and these may play an important role in its pathogenicity (31).…”
Section: Discussionmentioning
confidence: 99%